The rules for online clinical engagement in the COVID era (2020)
COVID-19 has generated a need to rapidly increase online consulting in secondary care, an area in which it has previously been underutilised. We sought to review the guidance around conducting remote consultations and found that while there is a large amount of information about the implementation of remote consultations at an organisation level, there is a paucity of high-quality papers considering the guidelines for online consultations alongside practical advice for their implementation at the individual level. We reviewed guidelines from reputable medical sources and generated practical advice to assist practitioners in performing safe and effective video consultation. Additionally, we noted reports in the literature of a lack of transparency and resulting confusion regarding the choice of telemedicine platforms. We therefore sought to summarise key characteristics of a number of major telemedicine platforms. We recognised a lack of clarity regarding the legal status of performing remote consultations, and reviewed advice from medicolegal sources. Finally, we address the sources of these individual uncertainties, and give recommendations on how these might be addressed systematically, so the practitioners are well trained and competent in the use of online consultations, which will inevitably play an increasingly large role in both primary and secondary care settings in the future.